The Norwegian Ombudsman for Children on child participation: Perceptions, impacts and dilemmas (Journal of Comparative Social Work, 2017)
The adoption in 1989 of the Convention on the Rights of the Child (CRC) has seen a quantum leap in the recognition- and expansion of initiatives to uphold children’s participation rights. The Ombudsman for Children plays an important role in promoting children’s rights, thus stressing the importance of authorities taking children’s opinions and experiences into consideration when making decisions which affect them. This article examines how the staff at the Ombudsman for Children in Norway understand and experience child participation through expert meetings and expert groups, in which children are regarded as the experts. The findings suggest that the existence of a consultative approach, where children’s views influence decisions, depends on the effectiveness of the Ombudsman’s representative function. While there is evidence of the recent growth of platforms for children to express their views, the core elements of participation largely remain monopolized by adults. We argue that active participation should be deliberately promoted beyond adult-led realms, and extended to ordinary contexts in which children interact with the society.